Activity profile, heart rate, technical involvement, and perceived intensity and fun in U13 male and female team handball players: Effect of game format - Madsen, M.; Ermidis, G.; Rago, V.; Surrow, K.; Vigh-Larsen, J. F.; Randers, M. B.; Krustrup, P.; Larsen, M. N. (Sports, 2019)
The aim of the study was to compare the activity pattern, heart rate (HR), technical involvement, and subjective perceptions in U13 boys and girls playing team handball in five game formats. Activity pattern, heart rate (HR), technical involvement, perceived fun, and exertion were recorded from four girls teams (n = 24) and four boys teams (n = 24) played during a 1-day tournament consisting of five different game formats of 15-min duration: Medium court size, 4v4 (M4v4), 5v5 (M5v5), and 6v6 (M6v6), and large court size, 5v5 (L5v5) and 6v6 (L6v6). Girls covered more total distance (TD) and high-speed running (HSR, 13-17.9 km·h-1) on the large court compared to the medium court (p < 0.05; ES = 2.1-3.1 and 1.2-2.5, respectively). Boys covered more distance as HSR and sprinting on the large court compared to the medium court, but only more TD on the large court compared to the medium court with the same number of players, (p < 0.05; ES = 1.0-1.8, 1.0-1.8, and 1.1-1.8, respectively). Team handball for U13 boys and girls is a high-intensity activity irrespective of court size. Increasing the court size with a fixed number of players increased the total distance and HSR, whereas manipulating the number of players on a fixed court size appears to influence technical involvement.